An association between water, sanitation, and hygiene (WASH) and prevalence of trachoma in Monze district of Southern Province, Zambia - Musonda Chikwanda (IWA Publishing, 2021)
This study aims to determine the association between water, sanitation, and hygiene, and the prevalence of trachoma in Monze district, Zambia. The overall prevalence of trachoma among residents of Monze district is 2.0% disaggregated as 3.4% for 1–9 age group and 1.1% for ≥10 age group. The findings reveal an association between trachoma eye infection and drinking water source from protected well/spring, and piped water. After adjusting for other variables, there was an association of drinking water from a protected well/spring (AOR 8.343, CI 1.126–61.803), piped water (AOR 4.127, CI 1.088–15.648), and piped water for washing (AOR 0.172, 95% CI 0.031–0.944.439). The presence of a hand wash facility was very low at 2.9% while hand washing agents were even lower at 0.41%. The study concludes that children are at a higher risk of trachoma prevalence. Other WASH aspects, such as adequacy of water, might be more important than the presence of potable water. The prevalence of trachoma in Monze is WASH focused. HIGHLIGHTS The research showed a significant need for attention 1–9 age group. Children are at a higher risk of trachoma prevalence.; The research reveals that having water from a protected water source if the water source is not easily accessible makes trachoma prevention difficult.; The findings serve as a foundation for the Monze Municipal Council and the community to advocate for more resources allocation to access to quality water.;